Analysis of phase detects altered timing of muscle activation in subjects with chronic shoulder pain. (February 2022) - Ginn, Karen A; Cathers, Ian; Boettcher, Craig; Halaki, Mark
Abstract: Optimal exercise therapy for shoulder pain is unknown due to limited information regarding specific changes in muscle function associated with pain. Timing of muscle activity with respect to movement (phase) can provide information about muscle activation patterns without requiring electromyography data normalization which is problematic in the presence of pain. The aim of this study was to determine if a phase measure is able to detect differences in the timing of shoulder muscle activation in subjects with chronic shoulder pain. Fourteen subjects with pain and 14 without pain were recruited. Electromyography from eight shoulder muscles was recorded. Approximately 20 cycles of small amplitude (∼30°) rapid shoulder flexion/extension was performed. A cross-correlation and spectrographic analysis provided a measure of phase. Welch's t-tests were used to compare mean phase angles between groups. Subjects with chronic shoulder pain had greater variability in the relative timing of muscle activation with significant differences found in the phase angles for pectoralis major, infraspinatus, supraspinatus, upper and lower trapezius and serratus anterior. This preliminary study indicates that the examination of the timing of muscle activation using a phase measure can identify significant differences in muscle function between normal subjects and those with chronic shoulder pain.